In vitro antimicrobial evaluation of toothpastes with natural compounds - Smolarek, Priscila de Camargo; Esmerino, Luis Antonio; Chibinski, Ana Cláudia; Bortoluzzi, Marcelo Carlos; dos Santos, Elizabete Brasil; Junior, Vitoldo Antonio Kozlowski (European Journal of Dentistry, 2015)
Objectives: This in vitro study evaluated the antimicrobial effects of commercial toothpastes containing natural compounds. Materials and Methods: The study groups were divided based on the natural compound present in the toothpaste composition: Sorbitol (I), tocopherol (II), mint (III), cinnamon/mint (IV), propolis/melaleuca (V), mint/açai (VI), mint/guarana (VII), propolis (VIII), negative control (IX), and the positive control (X). The antimicrobial properties of the toothpastes were tested using the disk diffusion method against oral pathogens: Streptococcus mutans, Pseudomonas aeruginosa, and Enterococcus faecalis. The resulting inhibition halos were measured in millimeters. Results: The data indicated that the bacteria responded differently to the toothpastes (P < 0.0001). The diameters of the inhibition halos against S. mutans were in decreasing order of efficacy: Propolis/melaleuca > mint/guarana > mint/açai > sorbitol > tocopherol > cinnamon/mint > propolis > mint (P < 0.001 vs. negative control). E. faecalis showed variable responses to the dentifrices in the following order of decreasing efficacy: Mint/guarana > propolis > sorbitol > mint/açai > tocopherol > cinnamon/mint > mint = propolis/melaleuca = negative control. The product with the highest antimicrobial activity was mint/guarana, which was significantly different than propolis/melaleuca, mint, cinnamon/mint, and tocopherol and negative control (P < 0.001). The statistical analysis indicated that propolis, sorbitol, and mint/açai did not show any differences compared to mint/guarana (P > 0.05) and positive control (P > 0.05). P. aeruginosa was resistant to all dental gels tested including positive control. Conclusion: The toothpastes with natural compounds have therapeutic potential and need more detailed searches for the correct clinic therapeutic application. The results from this study revealed differences in the antimicrobial activities of commercial toothpastes with natural compounds.
Keywords: Antimicrobial activity; dental gels; dentifrices; natural products; toothpastes